The Coming About of The American Dream - Jr., Martin LutherKing (THE PRIMARY TEACHER, 2008)
In the process of gaining our rightful place, we must not be guilty of wrongful deeds. Let us not seek to satisfy our thirst for freedom by drinking from the cup of bitterness and hatred. We must forever conduct our struggle on the high plane of dignity and discipline. We must not allow our creative protest to degenerate into physical violence. Again and again, we must rise to the majestic heights of meeting physical force with soul force. The marvellous new militancy which has engulfed our community must not lead us to a distrust of all white people, for many of our white brothers, as evidenced by their presence here today, have come to realise that their destiny is tied up with our destiny. And they have come to realise that their freedom is inextricably bound to our freedom. We cannot walk alone